Multiarm Star Polymers with Peripheral Dendritic PMMA Arms Through Diels-Alder Click Reaction - Durmaz, Hakan; Dag, Aydan; DAĞ, AYDAN; Onen, Ceyda; Gok, Ozgul; Sanyal, Amitav; Hızal, Gürkan; Tunca, Ümit (My University, 2010)
Dendritic 2- and 4-arm PMMA-based star polymers with furan-protected maleimide at their focal point, (PMMA)(2n)-MI and (PMMA)(4n)-MI were efficiently clicked with the peripheral anthracene functionalized multiarm star polymer, (a-anthryl functionalized-polystyrene)(m)-poly(divinyl benzene) ((alpha-anthryl-PS)(m)-polyDVB) through the Diels-Alder reaction resulting in corresponding multiarm star block copolymers: (PMMA)(2n)-(PS)(m)-polyDVB and (PMMA)(4n)-(PS)(m)-polyDVB, respectively. Molecular weights (M-w,M-TDGPC), hydrodynamic radius (R-h), and intrinsic viscosity (eta) of the multiarm star polymers were determined using three-detection GPC (TD-GPC). The high efficiency of this methodology to obtain such sterically demanding macromolecular constructs was deduced using H-1-NMR and UV-vis spectroscopy. (C) 2010 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 48: 4842-4846, 2010